2008
DOI: 10.1055/s-2008-1064935
|View full text |Cite
|
Sign up to set email alerts
|

The Use of 17 Alpha-Hydroxyprogesterone Caproate (17P) in Women with Cervical Cerclage

Abstract: Our objective was to compare the incidence of recurrent spontaneous preterm delivery (SPTD) in patients with cervical cerclage treated with weekly 17 alpha-hydroxyprogesterone caproate (17P) injections versus daily outpatient nursing surveillance (ONS) without 17P. Included in this retrospective cohort study were singleton gestations with cerclage placed at the discretion of the provider due to prior SPTD, delivering between January 1, 2004 and May 1, 2006. The study group (n = 232) consisted of women receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 4 publications
1
24
1
2
Order By: Relevance
“…Rafael et al , in a retrospective cohort study of 58 women with CL of < 25 mm at < 23 6/7 weeks' gestation, found that there was no significant differences in the incidences of spontaneous PTB < 35, < 32, or < 28 weeks' among women with a ultrasound indicated cerclage, regardless of whether or not they received 17OHP-C (15 in the 17OHP-C group vs. 43 in the no 17OHP-C group) during the current pregnancy. Their findings are similar to the results of two other studies concerning 17OHP-C in women with a cerclage in place (Berghella et al, 2010 andRebarber et al, 2008).…”
Section: Progestins and Short Cervixsupporting
confidence: 82%
“…Rafael et al , in a retrospective cohort study of 58 women with CL of < 25 mm at < 23 6/7 weeks' gestation, found that there was no significant differences in the incidences of spontaneous PTB < 35, < 32, or < 28 weeks' among women with a ultrasound indicated cerclage, regardless of whether or not they received 17OHP-C (15 in the 17OHP-C group vs. 43 in the no 17OHP-C group) during the current pregnancy. Their findings are similar to the results of two other studies concerning 17OHP-C in women with a cerclage in place (Berghella et al, 2010 andRebarber et al, 2008).…”
Section: Progestins and Short Cervixsupporting
confidence: 82%
“…Our review identified 6 studies that compared the use of progesterone plus cerclage to a reference group of women who received cerclage without progesterone [27]. All 6 studies used the synthetic progestin 17- α OHPC, and none utilized vaginal progesterone or systemic administration of bioidentical progesterone.…”
Section: Resultsmentioning
confidence: 99%
“…A prior study (16) reported the effect of 17P in women with cerclage, but could not distinguish between cerclage placed for history- or ultrasound- or even physical exam-indications. Another strength is the use of 17P was actually confirmed with measure of compliance.…”
Section: Commentmentioning
confidence: 95%